(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Ika is one of the minor ethnic groups in Delta State, Nigeria. It has a total land mass of about 1150 km2 and an approximate population of 259,850 (1991 census). The relationship between the Ika culture and „Ozu‟ consumption is well known. „Ozu‟ is an alcoholic liquor produced from palm juice. It is generally loved and enjoyed by the Ika people. The long association with and permissive behavior to „Ozu‟ ingestion may not be without problems. This preliminary research therefore attempts to highlight some of the social, economic and health problems elicited by „Ozu‟ consumption in Ika land.